A bibliometric analysis of anxiety and depression among primary school students - Fu, Jian Nan; Yu, Wen Bing; Li, Shuo Qi; Sun, Wen Ze (Frontiers in Psychiatry, 2024)
Background Rising anxiety and depression in primary school students adversely affect their development and academics, burdening families and schools. This trend necessitates urgent, focused research within this young demographic. This alarming trend calls for a systematic bibliometric analysis to develop effective preventative and remedial strategies Objectives This study aims to identify and analyze the prevailing research hotspots and emerging trends concerning anxiety and depression in primary school students, thereby furnishing a foundational reference for future academic endeavors in this area. Methods This study uses the Web of Science (WOS) Core Collection database as the data source, focusing on literature published between 2013 and 2023 concerning anxiety and depression in primary school students. An initial search identified 1852 articles, which were then manually screened to exclude duplicates, conferences, announcements, and unrelated literature, resulting in 1791 relevant articles. The analysis, executed on December 31, 2023, employed CiteSpace and Vosviewer tools to assess various bibliometric indicators including authorship, country, institutional affiliations, publication trends, keyword frequency, and citation analysis. Results The analysis revealed a corpus of 1,791 English-language articles, with a discernible upward trend in publications over the decade. The USA and China were the leading countries in this field, with 482and 272 papers, respectively. The research predominantly addresses the etiological factors of anxiety and depression, various intervention strategies, and the comorbidities associated with these conditions in the target population. Key research focuses have been identified in areas such as suicidal thoughts, bullying in schools, the impact of COVID-19, mindfulness interventions, and anxiety related to mathematics. Future research is projected to increasingly focus on the effects of mathematics anxiety on the psychological and behavioral outcomes in students. Conclusion This study provides a critical visual and analytical overview of the key research areas and trends in the field of anxiety and depression among primary school students. It underscores the necessity of concentrating on the underlying causes and potential interventions. Such focused research is imperative for mitigating the mental health challenges faced by young students and enhancing their educational and developmental outcomes.